Evaluating Unenhanced Multidetector Computed Tomography of Kidneys, Ureters and Bladder (CT KUB) as the Initial Imaging Service in Suspected Acute Renal Colic Patients - Saleem, Nida; Balooch, Salahuddin; Qayyum, Adil; Afzal, Tayyaba; Niazi, Najam Us Saqib Khan; Adil, Ruqqayia (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the role of unenhanced multidetector computed tomography (CT) of kidneys, ureters and bladder (KUB) in the initial imaging of suspected acute renal colic. Study Design: Retrospective longitudinal study. Place and Duration of Study: Combined Military Hospital, Kharian Pakistan, from Jan 2020 to Jan 2021. Methodology: One hundred and thirty-eight cases of suspected acute renal colic underwent CT-KUB. The demographic,radiological, clinical, and follow-up data were recorded for each patient. Results: There were 88(51.8%) males and 82(48.2%) females in the present study, with a mean age of 50.86±18.57 years. Out of 170 patients, only 138(81.17%) were indicated with acute findings, whereas 32(18.82%) individuals showed no acute findings.The mean stone size was found to be 4.77±0.98mm. Most of the stones had a location near the pelvic brim (n=47; 34.15%). Conclusion: The use of CT KUB should be encouraged for the evaluation of renal colic. Keywords: Acute renal colic, Computed tomography (CT), Computed tomography of Kidneys, ureter and bladder (CT-KUB).